Brain and mood changes over 2 years in healthy controls and adults with heart failure and ischaemic heart disease - Almeida, O.; Garrido, G.; Etherton-Beer, C.; Lautenschlager, N.; Arnolda, L.; Alfonso, Helman; Flicker, L. (2013)
Aims: Heart failure (HF) has been associated with cognitive dysfunction, a high prevalence of mood disorders, and a relative loss of grey matter in several brain regions. This study aimed to determine if, compared with controls with and without ischaemic heart disease (IHD), adults with HF show evidence of progressive loss of cerebral grey matter, and whether morphological changes are associated with changes in cognition, depression and anxiety symptoms over a follow-up period of 2 years. Methods and results: This was a 24-month longitudinal study of 19 participants with systolic HF, 43 with IHD, and 45 controls. Subjects were older than 45 years and free of cognitive impairment at the start of follow-up. We acquired magnetic resonance images and used Statistical Parametric Mapping version 8 (SPM8) to investigate changes in the distribution of cerebral grey matter volume over time. We used the Cambridge Cognitive Examination of the Elderly (CAMCOG) and the Hospital Anxiety and Depression Scale (HADS) to assess 2-year changes in cognitive function and mood. Changes in total grey matter volume and cognitive function were similar across the three study groups, but participants with HF showed evidence of increasing severity of anxiety and depressive symptoms. HF was associated with subtle regional loss of grey matter in the right and left thalamus, left caudate, left and right posterior cingulate, left and right parahippocampal gyri, left superior and middle temporal gyri, and right inferior parietal lobule compared with controls and, to a lesser extent, participants with IHD. Conclusion: HF and IHD are not associated with a disproportional loss of cerebral grey matter or cognitive decline over 2 years compared with cardiologically healthy controls. Adults with HF experience increasing symptoms of anxiety and depression over 2 years compared with controls, and this increased vulnerability is associated with a relative loss of grey matter in brain regions that are important for the modulation of emotions. © The Author 2013.